2012
DOI: 10.1175/jcli-d-11-00068.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variation of the Late Fall Rainfall in Central Vietnam

Abstract: The heavy rainfall/flood (HRF) event in central Vietnam usually occurs in October-November, the maximum rainfall season. This rainfall maximum undergoes a distinct interannual variation, opposite the interannual variation of sea surface temperature (SST) anomalies averaged over the NOAA Niñ o-3.4 area-DSST(Niñ o-3.4)-but coincident with the intensification (weakening) of the low-level easterlies at 158N and westerlies at 58N. The changes of low-level zonal winds reflect the strengthening (weakening) of the tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 29 publications
8
94
0
Order By: Relevance
“…5). In turn its rainfall is largely due to tropical cyclones and cold surges (Chen et al 2012;Yokoi and Matsumoto 2008). Combining these PDF results and the forecast skill results discussed in Sect.…”
Section: Temporal Verification For Subregionssupporting
confidence: 55%
“…5). In turn its rainfall is largely due to tropical cyclones and cold surges (Chen et al 2012;Yokoi and Matsumoto 2008). Combining these PDF results and the forecast skill results discussed in Sect.…”
Section: Temporal Verification For Subregionssupporting
confidence: 55%
“…The period of which was estimated based on the GPCP data. It is known that the precipitation corresponds with the convergence of the vertically integrated water vapor flux (Chen et al 2012). In the fields of <θe> and -∂<θe>/∂y, the climatological BF in JRA-25 extends along the latitudes of Japan in the EA-WNP sector (Fig.…”
Section: Baiu Front As a Boundary Between The Tropics And Mid-latitudmentioning
confidence: 99%
“…There is room for more research to understand the formation and the organization of these smaller but more frequent systems. While Chen et al (2012) showed that the interannual variation in rainfall in the region is related to the synoptic-scale cyclonic disturbances over and around the South China Sea, the mechanisms through which mesoscale convective systems can develop within the disturbances have not been clarified. Given that there are few diagnostic or dynamical analyses on this topic, we shall explore the mechanism behind the development of the Borneo vortex over the equatorial South China Sea and the associated generation and organization of deep cumulus convection.…”
Section: S Koseki Et Al: Borneo Vortex and Mesoscale Convective Raimentioning
confidence: 99%